The role of grazer predation strategies in the dynamics of consumer-resource based ecological models - Cropp, R; Moroz, I; Norbury, J (Elsevier, 2017)
We analyse a simple plankton system to provide a heuristic for more complex models such as Dynamic Green Ocean Models (DGOMs). Zooplankton foraging is either by generalist grazers that consume whatever they bump into or specialist grazers that actively seek particular prey. The zooplankton may further be classified as either facultative grazers that can survive on any of their prey or obligate grazers that depend on the presence of specific prey. A key result is that different prey dependencies can result in dramatically different impacts of grazing strategies on system outcomes. The grazing strategy can determine whether a system with obligate grazers will be stable, have regular, predictable cycles or be chaotic. Conversely, whether facultative zooplankton functioned as specialist or generalist grazers makes no qualitative difference to the dynamics of the system. These results demonstrate that the effect of different grazing strategies can be critically dependent on the grazer's dependency on specific prey. Great care must be taken when choosing functional forms for population interactions in DGOMs, particularly in scenarios such as climate change where parameters such as mortality and growth coefficients may change. A robust theoretical framework supporting model development and analysis is key to understanding how such choices can affect model properties and hence predictions.